Великорусский пахарь и особенности российского исторического процесса - Милов Леонид Васильевич (Росспэн, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 41523 / Цена: / Сис.шифр: 63.3(2)46 / Авт.знак: М 60 / ГРНТИ: 03.23.31 / ББК: 63.3(2)463-283